Recent developments in functional discourse grammar - Keizer, Evelien; Olbertz, Hella, 1953- (Studies in language companion series ;, 2018)
This volume presents a collection of papers using the theory of Functional Discourse Grammar (FDG) to analyse and explain a number of specific constructions or phenomena (external possessor contructions and binominal constructions, negation, modification, modality, polysynthesis and transparency) from different perspectives, language-specific, comparative and typological. In addition to applying the theory to the topics in question, these papers aim to contribute to the further development of the theory by modifying and extending it on the basis of new linguistic evidence from a range of languages, thus providing the latest state-of-the-art in FDG. The volume as a whole, however, does more than this, as separately and together the papers collected here aim to demonstrate how FDG, with its unique architecture, can provide new insights into a number of issues and phenomena that are currently of interest to theoretical linguists in general.